2015
DOI: 10.1038/nature15376
|View full text |Cite
|
Sign up to set email alerts
|

Microenvironment-induced PTEN loss by exosomal microRNA primes brain metastasis outgrowth

Abstract: Summary Development of life-threatening cancer metastases at distant organs requires disseminated tumor cells’ adaptation to and co-evolution with the drastically different microenvironments of metastatic sites1. Cancer cells of common origin manifest distinct gene expression patterns after metastasizing to different organs2. Clearly, the dynamic interplay between metastatic tumor cells and extrinsic signals at individual metastatic organ sites critically impacts the subsequent metastatic outgrowth3,4. Yet, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
869
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,015 publications
(893 citation statements)
references
References 30 publications
18
869
1
5
Order By: Relevance
“…Given a positive input from PKB towards IKK activation, it is tempting to speculate that PKB activation may positively regulate CCL2 expression. Indeed, expression of CCL2 is tightly controlled by NF-κB signaling partially through PKB activation in a PTEN-loss brain tumor model [105]. Furthermore, in an EMT induced immunosuppressive condition, CCL2 expression is regulated by the transcription factor Snail [106], which itself is negatively regulated by GSK3β, a direct target of PKB.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%
“…Given a positive input from PKB towards IKK activation, it is tempting to speculate that PKB activation may positively regulate CCL2 expression. Indeed, expression of CCL2 is tightly controlled by NF-κB signaling partially through PKB activation in a PTEN-loss brain tumor model [105]. Furthermore, in an EMT induced immunosuppressive condition, CCL2 expression is regulated by the transcription factor Snail [106], which itself is negatively regulated by GSK3β, a direct target of PKB.…”
Section: Pkb Regulated Macrophage Functionmentioning
confidence: 99%
“…miRNAs are resistant to nucleases due to their small size and the fact that in body fluids, they are likely protected in extracellular evesicles (EVs) or bound to protein or high‐density lipoprotein (HDL) binding partners (Brase, Wuttig, Kuner & Sultmann, 2010; Cortez et al., 2012; Reid, Kirschner & van Zandwijk, 2011; Wagner et al., 2013). This reservoir of miRNAs may transit to other cells and tissues where in some cases they influence gene regulation and may play a role in physiology and pathology (Hergenreider et al., 2012; Wei et al., 2017; Zhang et al., 2010, 2015). Earlier, we found that several circulating miRNAs are lower in abundance as humans age (Noren Hooten et al., 2010, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies indicate that exosomes are actually involved in different phases of carcinogenesis and tumor development. [48][49][50][51][52][53][54][55] From the perspective of tumor-initiating property, Melo et al 17 demonstrated that the non-tumorigenic MCF10A cells formed tumor mass in nude mice when co-injected with cancer cell-derived exosomes, and Dicer blocking in these exosomes could reduce tumor formation. This oncogenic conversion of MCF10A cells attributes to precursor microRNAs (pre-miRNAs), along with Dicer, AGO2 (Argonaute2), and TRBP (HIV-1 TAR RNA binding protein) in exosomes of cancer cells.…”
Section: Biological Functions In Tumorigenesismentioning
confidence: 99%
“…In the respect of tumor metastasis, Zhou et al 51 showed that breast cancer-derived exosomes destroyed vascular endothelial barrier to facilitate metastasis by targeting the tight junction protein ZO-1 via exosomal miR-105. Zhang et al 52 revealed the role of exosomal cargo in tumor metastasis by conducting the following PTEN experiment. PTEN loss could promote the tumor-cell dissemination in the brain since PTEN is an important tumor suppressor.…”
Section: Biological Functions In Tumorigenesismentioning
confidence: 99%